Cyber-security: An analysis of the risk placed on the right to privacy by technological innovation - Mwerebi i, Sean Kabuth (Strathmore University, 2021)
The internet has become the primary source of information access and communication in most if not all the countries in the world. It has made the world into a global village that has eased communication from different locations on earth and made it seem as if everyone is connected. It has indeed made the world evolve into a dimension very few envisioned. However, with this evolution comes a risk to the basic and fundamental human rights that have been developed overtime to protect human beings. The vast number of constitutions in the world provide for different yet very similar fundamental rights and freedoms that ensure human beings are protected. Amongst these many fundamental rights is the right to privacy which for a long time has been regarded to as a fundamental human right however, the development of technology and the internet is having a negative impact on said right. Data mining is amongst the many technological innovations that pose such a threat to the right to an individual’s privacy. Data mining applications involve vast amounts of data, which are likely to have originated from diverse, possibly external, sources. Thus the quality of the data cannot be assured. Moreover, although data pre-processing is undertaken before the execution of a mining application to improve data quality, people conduct transactions in an unpredictable manner, which can cause personal data to expire rapidly. When mining is executed over expired data inaccurate patterns are more likely to be revealed. Data mining by governments and private institutions can result in inaccurate representation of an individual due to inaccurate data consolidation. Data mining for a fact is generally a useful resource as it assist in following up on issues such as tax evasion and terrorism probabilities however the collection of personal data from an individual without the individual’s knowledge on such collection may result in inaccurate data projection which may be harmful to an individual. This research seeks to analyze this risk and how it has come about and consequently find a solution to ensure privacy rights are protected in the online atmosphere as much as they are in the real world. The research also seeks to analyze policies put into place by North America and different common law countries such as the United Kingdom in comparison with Kenya and how they regulate the internet to ensure that data protection is maintained. This analysis will hopefully result in recommendations for the establishment of laws and policies to ensure Kenyan citizens enjoy a safe space when they use the internet for their personal and or work-related matters
Proposal submitted in partial fulfillment of the requirements of the Bachelor of Law Degree, Strathmore University Law School